OAUNI photometry of SN 2023gfo - Pereyra, Antonio (2023)
Multiband photometry of Type II SN 2023gfo on 2023-05-24 (UT) was gathered with the OAUNI 51cm telescope at Huancayo Observatory, Peru. CCD imaging using VRI filters was performed under non-photometric conditions (seeing ~1.8") and airmass lower than 1.6. Total integration times of (45x20s=900s) for V, R and I filters yielded: V = 15.60 +/- 0.01 on 2023-05-24.228 (UT); R = 15.33 +/- 0.03 on 2023-05-24.197; I = 15.12 +/- 0.05 on 2023-05-24-212.